Spatial Distribution of Coral Reefs in the Waters of Babi Island, Aru Islands Regency - Djerol, Hans; Abrahamsz, James; Sangadji, Masudin (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
This study analyzes the spatial distribution of coral reefs surrounding Babi Island, Aru Islands Regency, Indonesia. The research aims to understand the condition of the coral reefs, create coral reef maps, and monitor their health. Satellite imagery and transect surveys were used to determine coral reef area, species richness, and benthic cover. The results show that the coral reefs are more extensive in the western part of the island (129.91 hectares) compared to the southern part (56.5 hectares). A total of 96 species of stony coral were identified, representing 67.1% of the species found in the Aru Islands coastal waters. Fifty of these species are considered protected under IUCN classifications. The coral reefs in the western part of Babi Island are in good condition with a hard coral cover percentage exceeding 70%. The southern part of the island also has coral reefs in good condition, but with a slightly lower hard coral cover percentage.